Structural reforms in the European Union - Vespermann, David (2021)
In this thesis, I study different dimensions of the interaction between economic outcomes and EU economic governance with a specific emphasis on the framework for fiscal policy and fiscal stabilization. Each of the three chapters consists of a self-contained research article followed by the corresponding appendix. Chapters 1 and 2 refer to the institutional status quo and examine the impact of existing rules. By contrast, Chapter 3 takes a forward-looking perspective and considers the effects associated with a specific potential reform of the framework.
Keywords: Graue Literatur; Hochschulschrift